The influence of relationship quality and culture in the relations between exporter and distributor : the case of portuguese exports to Angola - Alves, Gisela Maria Maia (2013)
The objective of this research is to investigate the role of the relationship quality, cooperation and culture between Portuguese companies and their export market intermediaries in Angola. In particular, we aim to understand the importance that the quality of the relationship has in cooperation and the role of cultures in export activities. An important aspect of this study is precisely the fact that it includes an African country, where, in terms of the literature, there is a strong lack of studies. In terms of methodology we opted for qualitative analysis; we present the results of two case studies of Portuguese exporting companies and one case study of Angolan intermediate. In general, the results are that the business relationships are characterized by trust, commitment, cooperation, culture, similar values, as in the past, Angola belonged to Portugal there is easy communication because both countries share the same. Such factors will influence the trade relations between Portuguese exporters and their Angolan distributors.